“Sharing Wisdom=Compartiendo Sabiduría”: An Educational Program for the Older Latino Population in the Greater Harrisburg Area - Ana Patricia Aguilera Hermida (Adult Education Research Conference, 2014)
The purpose of this study was to implement a community-based educational program for mature Latino adults and to promote social justice through empowerment, democracy, and education on health. Findings indicate that participants acquired and shared knowledge, created social networks, and gained a sense of empowerment.